MENCEGAH BULLYING MELALUI PENDIDIKAN AGAMA ISLAM: ANALISIS PERAN GURU DAN SISWA DI AL-YUSUFIYAH - Husnul Hakki Daulay; Tongku Saputra; Wantri Gunawan Matondang (Ahsani Taqwim: Jurnal Pendidikan dan Keguruan, 2025)
The purpose of this study was to determine the role of Islamic religious education in preventing student bullying behavior in the Al-Yusfia school environment. Bullying is one of the widespread social problems in the educational environment and has a negative impact on students' psychological and academic development. It is expected that Islamic religious leadership can shape morality and character to form students who have morality and stay away from various behaviors such as bullies. This study uses a qualitative approach with a descriptive method where data is collected through observation, interviews and documents. The results of the study indicate that Islamic religious education plays an important role in the design of students' moral awareness through teaching materials, teacher examples, and religious activities integrated into school life. Internalization of Islamic values ​​such as compassion, mutual respect, and brotherhood causes students to show more tolerance and stay away from bullying behavior. In short, the development of Islamic religion in al-Yusufiyah plays an important role in preventing bullying, but requires support from all parties to ensure that the results are more optimal.